Presentation: Jesuits and Modernity - Deckmann Fleck, Eliane Cristina; Carvalho Viotti, Ana Carolina de [UNESP] (Univ Estadual Londrina, 2021)
It is about the multiple activities of the Society of Jesus, one of the most present - if not the most - religious orders in Brazil during the so-called colonial period, in the colonies of the Spanish Crown in America and in various territories to the east, such as Macau and Goa, in addition to the Iberian Peninsula itself, which the studies gathered here focus on. In addition to the major theme - the multiple activities of the Society of Jesus in Modernity - addressed in the articles gathered in this Section, there is another aspect that deserves to be mentioned, namely, the affiliation of its authors to the International Society of Jesuit Studies. The SIEJ is an international scientific organization that brings together scholars from the most varied scientific areas whose research interests focus on the production of critical knowledge about the Society of Jesus, in all aspects that concern this Order, throughout its history. of more than 450 years, in different areas of the world.
Keywords: Modernity; Jesuits; Historiography; Knowledge; Circulation